PENGEMBANGAN TEKNOLOGI SISTEM SMART MICROGRID DI SEKOLAH TINGGI TEKNIK PLN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Nowadays application of new and renewable energy as power plan renewable energy resources as power plant resource more and more increased. High penetration of renewable energy into the grid will influence the quality and reliability of the electricity system, due to the intermittent characteristic of renewable energy resources. The smart grid or microgrid technology has the ability to deal with this intermittent characteristic especially while these renewable energy resources integrated to grid in large scale, so its can improve the reliability and efficiency of that grid. We plan to implementation of smart microgrid system at School High Tehnik of PLN as a pilot project. Before the pilot project design, the feasibility study must be conducted. In this feasibility study, the renewable energy resources and load characteristic at the site will be measure. Then the technical aspect of this feasibility study will be analyze.This paper explained the analysis of thus feasibility study.